Health-related quality of life of patients with psoriasis: A pilot study in Vietnam - Ngan, Le Thi Kim; Yen, Dinh Hoang; Linh, Pham Thi Thuy; Hao, Nguyen Trong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Psoriasis is a chronic proliferative skin inflammation associated with an immune-allergic mechanism. Long-term treatment regimen and abnormal recurrences may negatively affect the patients' health-related quality of life (HR-QoL). In Vietnam, the HR-QoL of patients with psoriasis has not been fully and comprehensively researched. Objective: Evaluation of HR-QoL of patients with psoriasis and its related factors. Methods: Cross-sectional descriptive study was conducted using the structured 3-part questionnaire, including socio-demographic and clinical characteristics, Dermatology Life Quality Index (DLQI) and visual analogue scale (VAS). Patients with psoriasis treated at Ho Chi Minh City Hospital of Dermato Venerelogy and satisfying inclusion, exclusion criteria were chosen in the study. Face-to-face interview with patients has been conducted from January to March of 2018. Analyzing related factors was performed with relevant statistical tests using 95% confidence interval by SPSS software. Results: Study sample including 310 patients treated at Ho Chi Minh City Hospital of Dermato Venerelogy with the average age of 48.84 ± 16.27 years and 58.39% male. The mean DLQI score was 6.92 ± 3.89 points. Among 6 dimensions of QoL, symptoms and feeling dimension were affected by psoriasis most with the score of 2.99 ± 1.33 (moderate level), followed by treatment dimension (1.77 ± 1.24). Age, living place, occupation, and marital status were related factors to the overall DLQI scores. Limitations: The study did not clarify the relationship of pathological factors with HR-QoL of psoriasis patients. Conclusion: Psoriasis had moderate effect on Vietnamese patient's HR-QoL. Age, living place, occupation, marital status are related factors on the HR-QoL impairment of psoriasis.